Plasma neurofilament light chain in cognitively unimpaired late middle‐aged & older adult APOE ε4 homozygotes, heterozygotes, & non‐carriers from the Arizona APOE Cohort. (20th December 2022) - Ghisays, Valentina; Su, Yi; Malek‐Ahmadi, Michael H.; Jansen, Willemijn J.; Protas, Hillary D.; Chen, Yinghua; Lee, Wendy; Luo, Ji; III, Robert J. Bauer; Chen, Kewei; Caselli, Richard J.; Zetterberg, Henrik; et al.
Abstract: Background: APOE 4 gene dose, the number of apolipoprotein E ‐ɛ4 ( APOE 4) ɛ4 alleles in a person's genotype, is associated with higher Alzheimer's disease (AD) risk and younger median age at dementia onset. We previously found relationships between PET, plasma, and measurements of core AD CSF biomarkers in APOE 4 gene dose. Here, we characterize longitudinal neurofilament light chain (NfL) changes in the Arizona APOE cohort, including cognitively unimpaired participants, with longitudinal plasma NfL measurements in APOE 4 homozygotes (HMs), heterozygotes (HTs) and non‐carriers (NCs). Method: Plasma NfL measurements were performed at the University of Gothenburg using a Single molecule array (Simoa) immunoassay. Annual log‐transformed plasma NfL changes were compared with linear‐tend and univariate ANOVA adjusted for age, sex, and education in 45 HMs, 107 HTs, and 201 NCs who were cognitively unimpaired, 47‐85 years old and did not differ significantly in their age, sex, or educational level. Pearson r correlations with age and annual log‐transformed NfL changes were assessed in 353 participants with at least 2 visits (range 2‐6 visits with an average of ∼3) and an average follow‐up of ∼7 years (range 1‐12 years). Result: Annual log‐transformed NfL changes were linearly associated with APOE 4 gene dose (linear trend HM>HT>NC, P=0.01) and positively associated with age (r = 0.31, P<0.0001). Pairwise comparisons from the univariate ANOVA adjusted for age, sex, and education (P=0.001) showed significantly higher annual NfL changes in HM and HT groups versus NC controls (P=0.01). Conclusion: Age and APOE 4 gene dose are associated with greater annual plasma NfL changes in CU subjects close to their estimated ages at clinical onset. Studies are needed to better elucidate relationships between different Aβ, tau, inflammatory, and other CSF, or blood‐based biomarkers, and APOE 4 gene dose at other ages and in larger subject groups.